1999
DOI: 10.1074/jbc.274.44.31648
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Extracellular Signal-regulated Protein Kinase or c-Jun N-terminal Protein Kinase Cascade, Differentially Activated by Cisplatin, Sensitizes Human Ovarian Cancer Cell Line

Abstract: We have studied the roles of c-Jun N-terminal protein kinase (JNK) and extracellular signal-regulated protein kinase (ERK) cascade in both the cisplatin-resistant Caov-3 and the cisplatin-sensitive A2780 human ovarian cancer cell lines. Treatment of both cells with cisplatin but not transplatin isomer activates JNK and ERK. Activation of JNK by cisplatin occurred at 30 min, reached a plateau at 3 h, and declined thereafter, whereas activation of ERK by cisplatin showed a biphasic pattern, indicating the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
146
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(163 citation statements)
references
References 66 publications
9
146
2
Order By: Relevance
“…25 On the other hand, some reports suggest ERK activation by cisplatin could antagonize apoptosis of tumor cells. [32][33][34] Interestingly, although complex 8 was able to induce ERK activation in our study, the failure of selective ERK inhibition to counteract the toxicity of this Pt(IV) complex argues against the involvement of ERK in its cytotoxic action. Our data instead suggest that overproduction of ROI, well known for its ability to trigger cell death, 35 might be crucial for the antitumor effect of novel Pt(IV) complexes.…”
Section: Discussionmentioning
confidence: 68%
“…25 On the other hand, some reports suggest ERK activation by cisplatin could antagonize apoptosis of tumor cells. [32][33][34] Interestingly, although complex 8 was able to induce ERK activation in our study, the failure of selective ERK inhibition to counteract the toxicity of this Pt(IV) complex argues against the involvement of ERK in its cytotoxic action. Our data instead suggest that overproduction of ROI, well known for its ability to trigger cell death, 35 might be crucial for the antitumor effect of novel Pt(IV) complexes.…”
Section: Discussionmentioning
confidence: 68%
“…For example, ERK activation is reported to be necessary for cisplatin-induced apoptosis in lung cancer cells (Wang et al, 2000), cervical carcinoma cell lines (Wang et al, 2000;Yeh et al, 2002) and malignant TGCT cell lines (Schweyer et al, 2004a). In addition, inactivation of MEK/ERK by its inhibitors has been shown to prevent apoptosis in response to cisplatin leading to resistance (Wang et al, 2000;Yeh et al, 2002), although contradictory results have been reported (Hayakawa et al, 1999;Persons et al, 1999). In this study, we found that activation of the MEK/ERK pathway was associated with increased sensitivity to cisplatin-induced apoptosis in the cells with high levels of MAD2 expression (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation (36) was assessed by the addition of paclitaxel at the indicated concentrations for 48 hours 1 day after seeding test cells into 96-well plates. The number of surviving cells was determined 24 hours later by determination of A 490 of the dissolved formazan product after the addition of MTS {3-[4,5,dimethylthiazol-2-yl]-5-[3-carboxymethoxy-phenyl]-2-[4-sulfophenyl]-2H-tetrazolium, inner salt}for 1 hour as described by the manufacturer (Promega).…”
Section: Methodsmentioning
confidence: 99%